2021
DOI: 10.3390/app11115198
|View full text |Cite
|
Sign up to set email alerts
|

Relative Hand Grip and Back Muscle Strength, but Not Mean Muscle Strength, as Risk Factors for Incident Metabolic Syndrome and Its Metabolic Components: 16 Years of Follow-Up in a Population-Based Cohort Study

Abstract: Muscle strength is associated with health outcomes and can be considered an important disease predictor. There are several studies examining the relationship between hand grip strength (HGS) and metabolic syndrome (MetS). However, no results have been reported for long term longitudinal studies. In this study, we investigated the relationship between mean HGS, back muscle strength (BMS), relative HGS and BMS, and MetS. A total of 2538 non-MetS subjects aged 40–69 years (1215 women and 1323 men) in the Korean G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Of the 30 studies in 19 articles, 26 ( 12 , 14 , 15 , 17 , 37 50 ) were cross-sectional studies and 4 ( 50 , 51 ) were cohort studies. A total of 24 studies in 14 articles ( 12 , 14 , 17 , 38 43 , 47 51 ) originated from Asia [7 studies in 4 articles ( 14 , 42 , 43 , 50 ) from South Korea, 12 studies in 7 articles ( 12 , 38 , 39 , 47 – 49 , 51 ) from China, 4 studies in 2 articles ( 40 , 41 ) from Japan, and 1 study ( 17 ) from Singapore], 2 studies in an article ( 15 ) from the United States, 2 studies ( 37 , 44 ) from Australia, 1 study ( 46 ) from United Kingdom, and 1 study ( 45 ) from Brazil. The total sample size was 43,396 in the 30 studies (reported in 19 articles).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 30 studies in 19 articles, 26 ( 12 , 14 , 15 , 17 , 37 50 ) were cross-sectional studies and 4 ( 50 , 51 ) were cohort studies. A total of 24 studies in 14 articles ( 12 , 14 , 17 , 38 43 , 47 51 ) originated from Asia [7 studies in 4 articles ( 14 , 42 , 43 , 50 ) from South Korea, 12 studies in 7 articles ( 12 , 38 , 39 , 47 – 49 , 51 ) from China, 4 studies in 2 articles ( 40 , 41 ) from Japan, and 1 study ( 17 ) from Singapore], 2 studies in an article ( 15 ) from the United States, 2 studies ( 37 , 44 ) from Australia, 1 study ( 46 ) from United Kingdom, and 1 study ( 45 ) from Brazil. The total sample size was 43,396 in the 30 studies (reported in 19 articles).…”
Section: Resultsmentioning
confidence: 99%
“…Jamar [3 studies ( 44 46 )], Takei [16 studies in 9 articles ( 14 , 15 , 17 , 40 , 42 , 43 , 47 , 48 , 50 )], Smedley [1 study ( 37 )], Camry [1 study ( 12 )], WCS-100 [4 studies in 2 articles ( 49 , 51 )], and hydraulic hand dynamometer [1 study ( 38 )] were used to measure HGS. There were 4 studies in 2 articles ( 39 , 41 ) that did not specify the name of the handgrip dynamometer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations